Tinjauan Yuridis Penerapan Pasal 22 Undang-undang Tindak Pidana Korupsi Atas Dugaan Memberikan Keterangan Tidak Benar Dalam Sidang Praperadilan (Studi Kasus Putusan No. 30/pid.sus-tpk/2021/pn.kupang) - Matutina, Cicilia Adityani; Wilhelmus, Bhisa V; Amalo, Heryanto (Law Faculty, Nusa Cendana University, 2023)
This research aims to find out whether giving false information in a pre-trial hearing is a violation of 22 of the Corruption Crime Law and giving false information in a pre-trial hearing without a judge's determination and an official report on suspicion of giving false information. To answer the objectives of this research, we use normative research methods or library legal research, namely the methods or methods used in legal research which are carried out by examining existing library materials. The results of this research show that the witness did not violate Article 22 of the Corruption Crime Law regarding false testimony before the trial because there was no valid evidence to ensnare the witness in the trial which was proven, where in this case the prosecutor accused the witness before the trial with false testimony without showing valid evidence in the trial and also the detention of Ali Antonius SH, MH was considered wrong because Ali Antonius exercised his rights as an advocate which is regulated in article 1 point 1 of Law number 18 of 2003 concerning Advocates which was strengthened by a court decision where Ali Antonius SH, MH, Harum Fransiskus, Zulkarnain Djudje were declared free. The allegation of providing false information in a pretrial hearing in this case must go through a trial procedure where the process must go through a judge's determination and a report on the alleged giving of false information because the prosecutor carried out the detention without procedures in the pretrial and did not go through the professional code of ethics for advocates.